Capital Market Reaction to the Strengthening of the Rupiah Exchange Rate against the US Dollar Exchange Rate - Lubis*, M Zaky Mubarak; Putra, Gusti Dirga Alfakhri; Binti Mohamad, Zam Zuriyati (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
The purpose of this study is to analyze the response of Indonesian capital markets to differences in average abnormal returns and average trading volume activity before and after the strengthening of the IDR/USD exchange rate. This study is a quantitative study using the event study method. The sample used consists of the stocks included in the LQ45 index. the most active stocks with a large daily trading volume. Hypothesis testing and paired t-test. The results of the hypothesis test show that: there is no significant difference in the average abnormal returns before and after the strengthening of the rupiah against the US dollar because are sig. (2-tailed) value of 0.417 > 0.05; there is no significant difference in the average trading volume activity before and after the strengthening of the rupiah against the US dollar because sig. (2-tailed) value of 0.080 >0.05. Keyword: Market Reaction; Event Study; Abnormal Return; Trading Volume Activity; Exchange Rate